Geometric design of rotary retractable plate structures based on parallelogram closed-loop chain linkages. Issue 4 (March 2021) - Yu, Feng; Xu, Xian; Luo, Yaozhi
For large-span retractable roof structures, the mechanism should be simple and efficient for the convenience of motion control. The kinematic characteristics of parallelogram closed-loop chain linkages (PCCL) show that a set of the angulated beams of PCCL rotates around the fixed points, which is suitable for retractable structures. This paper focuses on the geometrical design of the rotary retractable plate structures (RRPS), which evolves from PCCL by replacing the rotation angulated beams with cover plates. Each plate of RRPS has a fixed support and all the plates rotate simultaneously with a single DOF. The fixed points used as supports for cover plates to improve the stability and simplify the motion control of the system restrict the open area of the RRPS. By adjusting the contact boundaries of the cover plates, an optimisation method is proposed to increase the open area of the RRPS after fully deployed. The design approach is successfully extended to both symmetrical and asymmetrical RRPS. An example is carried out to demonstrate the feasibility of the approach and a simple physical model is manufactured to validate the design result in the example.